Density functional theory calculations of large systems: Interplay between fragments, observables, and computational complexity. (4th October 2021) - Dawson, William; Degomme, Augustin; Stella, Martina; Nakajima, Takahito; Ratcliff, Laura E.; Genovese, Luigi
Abstract: In the past decade, developments of computational technology around density functional theory (DFT) calculations have considerably increased the system sizes which can be practically simulated. The advent of robust high performance computing algorithms which scale linearly with system size has unlocked numerous opportunities for researchers. This fact enables computational physicists and chemists to investigate systems of sizes which are comparable to systems routinely considered by experimentalists, leading to collaborations with a wide range of techniques and communities. This has important consequences for the investigation paradigms which should be applied to reduce the intrinsic complexity of quantum mechanical calculations of many thousand atoms. It becomes important to consider portions of the full system in the analysis, which have to be identified, analyzed, and employed as building‐blocks from which decomposed physico‐chemical observables can be derived. After introducing the state‐of‐the‐art in the large scale DFT community, we will illustrate the emerging research practices in this rapidly expanding field, and the knowledge gaps which need to be bridged to face the stimulating challenge of the simulation of increasingly realistic systems. This article is categorized under: Electronic Structure Theory > Density Functional Theory Software > Simulation Methods Structure and Mechanism > Computational Materials Science Abstract : The challenge of applying DFT to large systems. The systems being studied are large and complex, with significant uncertainty about their actual conformation. By using DFT, we can create coarse grained descriptions that describe the interactions of large fragments in order to gain insigh